The Development of Learning Media for the Kinetic Theory of Gases Using the ADDIE Model with Augmented Reality - Gusmida, Rifqa; Islami, Nur (FKIP-Universitas Riau, 2017)
For senior high school students, learning concepts in physics isincreasingly more difficult when the topic is abstract and cannot be seenwith the unaided eye. The research here utilized augmented realitytechnology and instructional design following the ADDIE model (analysis,design, development, implementation and evaluation) to develop learningmedia for physics, specifically the kinetic theory of gases. Preliminaryanalysis was conducted in a senior high school to evaluate the challengesstudents face when learning physics. The design of the media was based onaddressing problems that the students were having. Augmented realitytechnology was then utilized and the implementation aimed to incorporatethe physics concepts into the product. The media was evaluated by sixexperts. Finally, the learning media presented real-time 3D animation of gaskinetic theory with three basic competencies relevant to the topic. In thefinal validation, the results indicated that the developed learning media had avalidity value of 3.55 out of four-point scale and good quality outcomes. Assuch, the developed media regarding the kinetic theory of gases is valid andeffective for the process of learning and teaching. It is ready to be tested andused in actual learning environments.